Father Joe's Villages : how a one-stop-shop tackles homelessness in San Diego - Beckman, Sara Lynn; Thomas Springer, Susan (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
Father Joe's Villages (FJV) is a non-profit organization in San Diego, California, whose mission is to "prevent and end homelessness, one life at a time." FJV was founded by Father Joe Carroll in 1982 as a response to the lack of comprehensive offerings to support people experiencing homelessness. While focused on providing housing, FJV has also developed a wide variety of support services centered around four pillars of service-meeting basic needs through housing, meals, and basic humanitarian services; investing in children through family services and the Therapeutic Childcare Program; making health a priority through medical, dental, and behavioral health services; and strengthening self-sufficiency through employment support, education programs, vocational training, and chaplaincy. In 2018, FJV received a national award from the U.S. Department of Health and Human Services as a Health Center Quality Leader.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Public welfare; Homelessness